CONTINUOUS EVALUATION OF PHYSICAL KNOWLEDGE - KRIEG, Jaroslav; SMETANOVA, Dana (Trends in education, 2015)
In this paper we describe the way in which they were continuously evaluated students in the subject of Physics in logistics processes, feedback and motivational elements of evaluation. We discuss three different approaches in the evaluation of ongoing tests with testing at the blackboard, electronic testing and evaluation by voluntary seminar papers.
Keywords: current evaluation; motivation; feedback.